A vétőképtelen személy károkozásáért való felelősség - Varga, Nelli (Debreceni Jogi Műhely, 2015)
The new Hungarian Civil Code also modernizes the non-contractual liability law in several aspects. Even if the so-called general clause of non-contractual liability reamains unchanged, its contstitutive elements are regulated in detail in the new Civil Code. The new Code also introduces some new provisions with regard to liability for dameges caused by a person of lack of discretionary power. The objektive of this survey is to present these changes and to examine its possible impacts on judicial practice.